Impact of Changes in Infection Control Measures on the Dynamics of COVID-19 Infections in Schools and Pre-schools - Sombetzki, Martina; Lücker, Petra; Ehmke, Manja; Bock, Sabrina; Littmann, Martina; Reisinger, Emil C.; Hoffmann, Wolfgang; Kästner, Anika (Frontiers in Public Health, 2021)
Introduction: With the increased emergence of SARS-CoV-2 variants, the impact on schools and preschools remains a matter of debate. To ensure that schools and preschools are kept open safely, the identification of factors influencing the extent of outbreaks is of importance. Aim: To monitor dynamics of COVID-19 infections in schools and preschools and identify factors influencing the extent of outbreaks. Methods: In this prospective observational study we analyzed routine surveillance data of Mecklenburg-Western Pomerania, Germany, from calendar week (CW) 32, 2020 to CW19, 2021 regarding SARS-CoV-2 infection events in schools and preschools considering changes in infection control measures over time. A multivariate linear regression model was fitted to evaluate factors influencing the number of pupils, teachers and staff tested positive in following primary cases in schools and preschools. Results: We observed a significant increase in secondary cases in preschools in the first quarter of 2021 (CW8 to CW15, 2021), and simultaneously a decrease in secondary cases in schools. In multivariate regression analysis, the strongest predictor of the extent of the outbreaks was the teacher/caregiver mask obligation (B= -2.5; 95% CI: -3.7 to -1.2; p<0.001). Furthermore, adult index cases (adult only or child+adult combinations) increased the likelihood of secondary cases (B=1.4; 95% CI: 0.9 to 1.8; p<0.001). Conclusion: The present study indicates that outbreak events at schools and preschools are effectively contained by an obligation for adults to wear face masks.